Soft α-Open Sets and Soft α-Continuous Functions - Metin Akdag; Alkan Ozkan (Abstract and Applied Analysis)
We introduce soft α-sets on soft topological spaces and study some of their properties. We also investigate the concepts of soft α-continuous and soft α-open functions and discuss their relationships with soft continuous and other weaker forms of soft continuous functions. Also counterexamples are given to show the noncoincidence of these functions.